Effect of temperature on the stress corrosion cracking of zircaloy-4 in iodine alcoholic solutions - Gomez Sanchez, Andrea Valeria (2007)
Zircaloy-4 is susceptible to stress corrosion cracking (SCC) in solutions of iodine dissolved in different alcohols (methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol and 1-octanol). The crack propagation rate is known to decrease as the solvent molecular weight increases, as a consequence of steric hindrance. However, the mechanism that operates during SCC is still unknown. In the present work the effect of temperature on SCC susceptibility was evaluated in 1-butanol and 1-pentanol iodine containing solutions. The dependence of the crack growth rate with temperature follows an Arrhenius law, and the activation energy obtained from experimental data is consistent with a process controlled by volume diffusion of the active species (the iodine-alcohol complex) to the crack tip.